Robert Southey and his age: ageing, old age and the days of old - Pratt, Lynda (Edinburgh University Press, 2018)
Throughout a four-decade career, the controversial poet, historian, biographer and essayist Robert Southey explored the trajectories both of his own individual life and of the time and the society in which he lived. Using a range of published and unpublished sources, including Southey’s vast correspondence, this essay will track this preoccupation for the first time and consider its implications for understanding both of Southey and of Romanticism.